Cash Flow-Based Financial Performance Evaluation of PT Mayora Indah Tbk: A Ratio Analysis Approach (2023–2025) - Atika Amor (CV Edujavare Publishing, 2026)
This study aims to analyze the cash flow performance of PT Mayora Indah Tbk (MYOR) for the period 2023–2025 using seven cash flow ratios: Cash to Interest Coverage Ratio, Cash Flow Coverage Ratio, Total Debt Ratio, Cash to Current Liabilities Coverage Ratio, Operating Cash Flow Ratio, Capital Expenditure Ratio, and Cash Flow Adequacy Ratio. Data were sourced from the company's audited annual financial statements over four consecutive years. The analysis reveals a clear cyclical pattern in PT Mayora Indah Tbk's cash flow performance. The year 2023 represented the peak performance period, with all ratios at optimal levels: Cash to Interest Coverage Ratio reached 16.92x, Operating Cash Flow Ratio stood at 1.31x, and Cash to Current Liabilities Ratio was 1.04x — the only year in which cash balances exceeded total current liabilities. The year 2024 marked a stress point driven by aggressive expansion, causing net operating cash flow to turn negative (IDR 463.36 billion), resulting in near-universally negative ratio values. Nevertheless, the expansion successfully drove total asset growth of 24.5% to IDR 29.73 trillion. By 2025, the company demonstrated strong and consistent recovery. Operating cash flow returned to a positive IDR 3.51 trillion, with the Capital Expenditure Ratio reaching its highest level at 3.09x — signaling the completion of the major investment cycle and a transition to a consolidation phase. Cash balances reached a peak of IDR 5.85 trillion, with Cash to Current Liabilities at 0.93x. However, the Cash Flow Adequacy Ratio remained at 0.68x, indicating that the company has yet to achieve full cash self-sufficiency in simultaneously meeting working capital needs, capital expenditures, and dividend obligations. The company's capital structure proved prudent throughout the analysis period, with the Total Debt Ratio remaining stable at 36%–42%, well below the commonly cited risk threshold of 60%. These findings demonstrate that, despite temporary liquidity pressures from expansion, PT Mayora Indah Tbk maintains solid financial fundamentals with all ratios trending positively. This study provides practical implications for investors, creditors, and management in evaluating the cash flow capacity of manufacturing companies in an active growth phase.